The Structure of Phonological Networks and Social Identity of Heritage Languages - Raza, Mohd Hamid (JL3T (Journal of Linguistics, Literature and Language Teaching), 2020)
This paper provides the basic information of the phonological networks and social identity about the heritage languages. The phonological networks convey the classification of the sound systems, while the social identity declares the difference among the native speakers of the heritage languages. The problem is investigated that how a particular speech segment created the variation among the speakers of the different languages in the speech communities. The objective of this paper is to determine the unique segments of the heritage languages and how these segments clear the social identity of the speakers in a particular speech community. The researcher collected the sample of primary and secondary data from the gadgets and the speakers of the heritage languages. The sample of data goes to the social characteristics of ages between twenty and forty of the respondents both male and female. The data are collected through observation, interview and the available literature of the heritage languages. For the collection of primary data, the high quality of the tape recorder is used and put approach to the mouth of the respondents for the recording at the time of interview. After the data collection, it is analysed base on the aspects of phonetics and phonology to find out the social identity of the respondents. In the result, it is found out that one particular speech segment represented the social identity of the speakers. In the framework of conclusion, it is represented that Urdu has different types of the speech segments covered all the processes of production, transmission, and perception.